Using Modelling-Based Speaking Module for Informal Interaction Class to Support Self-Regulated Learning - Nurjanah, Ratih Laily; Saptanto, Deswandito Dwi; Dewi, Maya Kurnia (Universitas Negeri Semarang, 2021)
Teaching speaking is considered challenging during this outbreak era where lecturers and students cannot have a face-to-face meeting while in fact, students still need to get examples from lecturers related to pronunciation and intonation especially. A module of speaking for informal interaction is developed to support the process of teaching and learning speaking skills. This module comes with an audio-CD of daily expressions records spoken by a native speaker to give examples of standard pronunciation and intonation. This study aims to explain the steps used in the learning process using the module. It uses narrative design to describe the steps. The findings of the study implied that lecturers need to explain what the module is and how to use it followed by some steps; introducing lesson plan, playing audio-CD, imitating the records, practicing independently, working in pairs, reporting works, receiving feedback. By giving the model or examples in audio, students can repeat it as much as they need and whenever they need it. This study's implication is giving standardized materials using authentic materials to teach speaking skills with a self-regulated learning strategy.Ã‚Â